Analysis of the implementation of corporate level strategy in a South Afircan furniture retailer - Nkatsha, Thembinkosi Sydney (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
[Integrative Summary] This study is situated in the complex field of change management, and strategy execution. The study focuses on the corporate level restructuring of Ellerine Holdings Limited (EHL), subsequent to its acquisition by the micro lending financial institution African Bank Investments Limited (ABIL). The interest of the researcher was aroused by the uniqueness of the relationship. This was the first of its kind in a South African context, where a banker owned a furniture retailer. The restructuring was undertaken shortly after the acquisition. This research paper adopted a case study approach, in describing the restructuring initiative that took place in EHL, focusing on the period between January 2008 and the end of 2010/ 11 financial year on the 30th of September 2011. The case captures the significant phases of the restructuring including a background of (1) the protagonist, Toni Fourie (Chief Executive Officer), (2) EHL as the researched company, (3) the industry it operates in, and (4) the case content. Brief teaching notes have been provided to explain the teaching value of the case and to assist with its delivery in the classroom. Attention is drawn to a presentation by the protagonist in November 2011, named 'A CEO Insight' where he gave an overview and insights of the road travelled in restructuring Ellerine Holdings Limited, and more importantly highlights the following about the purpose and nature of the restructuring of the organisation. "¢ A plan to change the way the industry works. "¢ The creation of a profitable, stand-alone retail business through: o The sale of two companies, the closure of two companies and consolidating from thirteen to six brands. o Separating financial services from retail. o Moving the financial services component to African Bank, also a subsidiary of ABIL. o Redesigning the credit model. o Completion of twelve system changes. "¢ Over R600million reduction in cost "¢ A place where people want to work. The restructuring outlined above represents a major shake-up in many aspects of the corporation. The main challenge for Toni Fourie and his team was: how best could they restructure EHL to extract synergies between their two subsidiaries Ellerine Holdings Limited & African Bank to increase shareholders ' value at Group level. The case seeks to describe this in detail. The overarching strategy underpinning the restructuring of the researched corporation is premised on the price volume elasticity equation, by reducing the cost of credit, thereby driving pricing down within the brands, and facilitating more people having access to affordable credit. The case study of the restructuring is presented in Section 1. A review of relevant literature on strategy implementation is presented in Section 2, focusing on restructuring. Successful implementation of strategies only takes place with structures that are developed by organisations to support the achievement of their strategic objectives. Organisational architecture and design have a critical role to play in the execution of organisational strategies. Nadler and Tushman (1978) emphasise the importance of congruence in the organisational design, for the organization to not only deliver superior results but to sustain them over a period of time. Research by Okumus (2005) seems to tell us that the lack of credible framework to implement strategy, has contributed the high failure rate of strategy initiatives. Although this is a strategy implementation case, it also touches on aspects of leadership - mainly the architectural role - and the role, or influence of strategic leadership, in restructuring the corporation. The results of this research paper were achieved by following a specific research methodology. The aim of the research was to analyse the restructuring of the researched company at corporate level, having the following objectives in mind; "¢ Understanding the strategy. "¢ Analysing the design decisions in the light of the strategy chosen by the top management of Ellerine Holdings Limited. "¢ Analysing what monitoring and control measures had been designed to facilitate the corporate restructuring. Data was collected through documentation of the corporation that was made available to the researcher on request, as well as those that are in the public domain, and an interview with the CEO of the researched company. The interview was conducted after analysing the documentation (Hakim, 2000). The Methodology is detailed in Section 3. The researcher hopes that the case study will contribute to learning about business leadership and strategic management. The case should develop an understanding of the complexities related to strategy execution at corporate level, particularly the restructuring aspect of it.
Keywords: Reengineering (Management); Consolidation and merger of corporations -- South Africa -- Case studies; Organizational change -- Management